Effect of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Newton, Shane P.; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Newborn piglets are susceptible to iron deficiency because of insufficient stores of iron at birth. The dosage of iron used in the industry today is one 200mg injection of iron at time of piglet processing. Gleptoforte is an injectable iron that contains Gleptoferron and is utilized to prevent anemia in newborn piglets, but there is very little data that supports the correct dosage to use this product. The purpose of this study is to examine the impact of increasing Gleptoforte dosage on piglet performance. 336 newborn pigs, were used in a 21-d farrowing study where performance and blood parameters were evaluated based on increasing Gleptoforte dosages on suckling pigs. Three days after birth, all piglets were weighed and a total of 56 piglets per treatment, six barrows and six gilts per litter, were allotted to treatment in a completely randomized design. The treatments were as follows, a negative control of no iron injected, increasing levels of iron from Gleptoforte 50mg, 100mg, 150mg, 200mg, or 200mg + 100mg booster at d11 of farrowing. Piglets were weighed on d3, d11, and d21 to evaluate ADG during farrowing. One barrow per treatment per litter was utilized for blood collection via jugular venipuncture on data collection days. Blood Criteria was as follows, Hemoglobin (Hgb), Hematocrit, (Hct) Serum Fe, and Total Iron Binding Capacity (TIBC). ADG and BW increased as the dosage of Gleptoforte increased throughout all days of data collection (quadratic, linear; P<0.05). Yet, there were no sufficient evidence in performance differences during the three periods between the 200mg and 200mg with a booster (P>0.05). There was no significant difference in the Hgb levels during d3. But there was an increasing Hgb level during d11 and d21. When looking at Hct the levels were increasing on d11 and d21 with the 0mg treatment having the lowest and the 200mg treatment having the highest values respectively. For Serum Fe interaction was observed where serum Fe increased and increased on d21 with the 0mg treatment being the lowest and the 200mg treatment having the highest respectively. In conclusion, a lack of iron injection resulted in the poorest growth and blood parameters of iron status of suckling pigs as expected. The greatest growth performance occurred in the administration of 100mg of Gleptoforte (quadratic, linear; P<0.05). Lastly, the booster injection of 100mg + 200mg has no impact on growth performance compared to 200mg alone.
Keywords: Fall 2017